Thermal Behaviour Studies of Solid State Lanthanide (III) and Yttrium (III) Compounds of Cinnamylidenepyruvic Acid in an Atmosphere of Air - Oliveira, José Dilson Silva de [UNESP]; Leles, Maria Inês Gonçalves; D Assunção, Lazaro Moscardini; Melios, Cristo Bladimiros [UNESP]; Ionashiro, Massao [UNESP] (Sociedade Brasileira de Química, 1999)
Compostos Ln-CP foram preparados no estado sólido, onde Ln representa os lantanídios trivalentes (exceto promécio) e itrio e CP é o cinamalpiruvato. As técnicas termogravimetria (TG), calorimetria exploratória diferencial (DSC), difratometria de raios X e complexometria foram utilizadas para caracterizar e estudar o comportamento térmico destes compostos. Os resultados proporcionaram informações com respeito a desidratação, estabilidade e decomposição térmica.

Solid state Ln-CP compounds, where Ln represents trivalent lanthanides (except for promethium) and yttrium, and CP is cinnamylidenepyruvate, were prepared. Thermogravimetry (TG), differential scanning calorimetry (DSC), X-ray diffraction powder patterns and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results provide information about dehydration, thermal stability and thermal decomposition.
Keywords: lanthanides and yttrium; cinnamylidenepyruvate; thermal behaviour